(untitled) (Research, Society and Development, 2023)
Between 2008 and 2021, 1,539,536 patients were hospitalized due to diseases of the appendix (AD). AD can be of inflammatory and neoplastic origin, with the neuroendocrine tumor being the most prevalent neoplastic cause, and acute appendicitis, the main inflammatory etiology. This is an ecological study of time series of mortality in Brazil. Data were collected from the Hospital Information System (SIH-SUS) made available by DATASUS. The variables analyzed were the crude mortality rate and specific mortality rates, according to gender, age group and region of the country, due to appendicitis in Brazil. 5676 deaths were identified in Brazil. It is concluded when evaluating the linear regression rates that Brazil presents a predominance of stability profile. Likewise, an ambivalent behavior stands out, with stability in the extreme age groups and a reduction in the 20-29 age group, in addition to a downward trend in women and stability in men.